Physico-chemical and pharmaco-technological research at a substantiation of rational composition and technology of suppositories «indoxam» - Zaychenko, Volodymyr; Ruban, Olena; Maslii, Yuliia; Gerbina, Natalia (ScienceRise: Pharmaceutical Science, 2018)
The development of new highly effective drugs in the form of rectal suppositories for the treatment of diseases of the prostate gland does not lose its relevance today, since the number of patients with these pathologies is increasing every year. These diseases adversely affect the physical, psychological health and quality of life of men in general. An important issue in the substantiation of the composition and development of the technology for the production of suppositories is the study of their physico-chemical and pharmaco-technological properties that directly affect their consumer qualities and the mode of the technological process. Aim of the work was the study of the physico-chemical and pharmaco-technological properties of the combined rectal suppositories "Indoxam" to select rational conditions of the technological process. Materials and methods. In order to substantiate the composition and technology of the combined rectal suppositories “Indoxam”, modern physicochemical (thermal analysis, rotational viscometry method) and pharmaco-technological (disintegration suppositories, resistance to degradation) studies were used according to the requirements of SPHU. Results. To select the optimal ratio of polyethylene oxides in the suppository base, the resistance of suppositories to destruction and the disintegration time of samples made with different amounts of PEO-1500 and PEO-400 were studied. To determine the optimal technology for the preparation of the drug, a study was made of the decomposition temperature of the API, which makes it possible to determine the temperature regimes for the preparation of suppositories and the introduction of active substances into the base without the risk of destroying the structure of substances and changing their pharmacological actions. Since, under the influence of mechanical, thermal, and other actions, several types of destruction undergo suppositories, their rheological characteristics are also investigated. Conclusions. The results of pharmaco-technological research allowed to substantiate the optimal ratio of polyethylene oxides in suppository basis. The conducted thermogravimetric analysis of API and suppositories «Indoxam» established the thermal stability of substances and the absence of chemical interaction between the components in the composition of rectal drug. According to the rheological characteristics, the system identified the thixotropy and the optimal pouring temperature of the suppository mass